The Variations in the Altitudes Between the Sea Level and Ajloun Impact Heart Variables, but not Angiotensin Ii - Sweis, Jehan Fayez; Haddad, Reema Kamal; Salmoneh, Abdallah T; Aljabra, Rabia Jamil; Alrefai, Taghreed A; Abeeleh, Mahmoud Abu; Abeeleh, Jaafar Abu; Al-Shehabat, Mustafa Ahmad; Alkhatib, Ahed J (European Scientific Journal, ESJ, 2016)
Background: hypertension affects many people worldwide and it is highly prevalent in Jordan. Living at different areas with different attitudes may have impacts in hypertension. Study objectives: to identify the prevalence of hypertension in two areas in Jordan with different attitudes and to determine the impact of attitudes in hypertension and angiotensin II to be able to determine the appropriate antihypertensive drug for such population. Methodology: a cross-sectional study design was conducted to collect data from participants. The study included 1000 participants, 500 from each area. A constructed questionnaire was used in this study. Blood samples were taken from participants to assay for angiotensin II. Blood pressure was measured for all patients. Data was analyzed using SPSS version 20. Data was presented as means, frequencies, percentages. The relationship between variables was examined using independent T-test. Significance was considered at alpha level 0.05). Conclusions: living in high altitude is associated with increased potential to have increased levels of cardiac parameters independently of the level of angiotensin II and the therapeutic options for patients with hypertension should be taken into account.